Kajian Literatur Bioaktivitas, Fitokimia, dan Potensi Dermatologis Carthamus tinctorius L. - Virsa Handayani; Akrom; Aktsar Roskiana Ahmad (Jurnal Penelitian Pendidikan IPA, 2026)
This study systematically reviews the bioactivity, phytochemistry, and dermatological potential of Carthamus tinctorius L. using a structured synthesis of nine eligible research articles. The purpose of this review is to consolidate scientific evidence regarding the antioxidant activity, phytochemical composition, molecular mechanisms, and skin-related relevance of this plant across diverse study designs. The findings indicate that Carthamus tinctorius contains polysaccharides, phenolic compounds, flavonoids, and fatty acids that exhibit strong antioxidant activity, enzyme inhibition, and cellular protective effects. Several studies demonstrate its ability to modulate oxidative pathways, inhibit collagen-degrading enzymes, and support skin barrier integrity, highlighting its promising dermatological applications. Variations in bioactivity were influenced by genotype, environmental conditions, and extraction techniques, underscoring the importance of plant origin and processing methods. Overall, the review concludes that Carthamus tinctorius possesses significant potential as a natural source of therapeutic compounds relevant to skin health, anti-aging applications, and future product development. This synthesis also identifies methodological gaps that may guide further experimental, molecular, and formulation-based research.